Cultural Acculturation in Rimpu and Sanggentu Clothing of the Mbojo Tribe - Awal Putra Suprianto (Institut Agama Islam Negeri Kendari, 2025)
This study aims to understand the process of cultural acculturation and the dynamics of structure and agency in the practice of Rimpu and Sanggentu fashion among Mbojo women in Bima and Dompu, West Nusa Tenggara. The research questions focus on how the use of Rimpu reflects the process of cultural acculturation, how individual and collective agency influences social structure, and how the symbolization of fashion shapes cultural identity. The method used is a qualitative ethnographic approach with participant observation techniques, in-depth interviews, and visual documentation. The results of the study indicate that Rimpu and Sanggentu are products of hybridization between local culture and Islamic values, mediated by agency, both from elites such as Sultan Bima I and from local women. New social structures are not formed through coercion, but through interaction between humans so that they can provide meaning and ideas that are created and used periodically or repeatedly. This study contributes to the development of Giddens' structuration theory in the context of local Indonesian culture and encourages an approach to cultural preservation that is oriented towards meaning and active community participation.